Separation and identification of peptides from dry-cured Jinhua ham. (10th January 2018) - Zhu, Chao-Zhi; Tian, Wei; Li, Miao-Yun; Liu, Yan-Xia; Zhao, Gai-Ming
ABSTRACT: A long ripening period is essential for the production of dry-cured ham. This ripening process results in the generation of a large number of small peptides that are responsible for the ham's flavour. In this study, peptides extracted from Jinhua ham were separated and purified using a tangential flow filter and Sephadex G-25 gel filtration chromatography and identified using liquid chromatography-tandem mass spectrometry. Sixty-three peptides were identified within the range between 227.1 and 1540.8 Da, including 10 dipeptides, 14 tripeptides, 12 tetrapeptides, eight pentapeptides, eight hexapeptides, four heptapeptides, one octopeptide, three nonapeptides, one decapeptide, one dodecapeptide, and one tridecapeptide. The most abundant peptides (and their relative peak areas) were Leu-Pro-Lys (10.49%), Ser-Gly-Leu (8.72%), Ala-Ala-Pro (7.36%), Val-Glu (5.62%), Pro-Leu (3.83%), Ser-Gly-Val (3.77%), Ala-His (3.40%), Ala-Arg (3.37%), and Leu-His-Ala (3.03%). The peptide sequence results provide novel information that contributes to a better understanding of proteolysis and fundamental peptide characterizations. Abbreviations: L, Leu; P, Pro; K, Lys; S, Ser; G, Gly; L, Lys; A, Ala; V, Val; E, Glu; H, His; R, Arg; T, Thr; C, Cys; I, Ile; N, Asn; D, Asp; Q, Gln; Y, Tyr; M, Met; W, Trp; F, Phe; DPP, dipeptidyl peptidase; TPP, tripeptidyl peptidase; LAP, Leu aminopeptidase; AAP, Ala aminopeptidase; RAP, Arg aminopeptidase; TFF, tangential flow filter